Skin colonization by Staphylococcus aureus in hemodialysis patients with pruritus and the effect of Staphylococcus aureus‐secreted α‐toxin on filaggrin expression - Tsai, Yen‐Yu; Chen, Ying‐Jung; Chang, Long‐Sen; Wu, Cheng‐Ching (Journal of dermatology, 2024)
Staphylococcus aureus (S. aureus) commonly reside on human skin in residents in long‐term care facilities, yet its colonization and impact on the skin of hemodialysis (HD) patients have yet to be studied. The aim of the present study was to investigate the colonization of S. aureus on the skin of pruritic and non‐pruritic HD patients, and the influence of S. aureus and S. aureus‐secreted α‐toxin on skin barrier function‐related protein expression. In this study, a higher relative S. aureus count in pruritic HD patients compared to non‐pruritic HD patients and healthy subjects were revealed by real‐time polymerase chain reaction. S. aureus and α‐toxin decreased mRNA and protein expression levels of aryl hydrocarbon receptor (AHR), ovo‐like transcriptional repressor 1 (OVOL1), and filaggrin (FLG) in keratinocytes. In addition, anti‐alpha‐hemolysin (anti‐hla) was used as an α‐toxin neutralizer, and it successfully abrogated S. aureus‐induced AHR, OVOL1, and FLG mRNA and protein expression downregulation. Mechanistically, α‐toxin could decrease FLG activity by preventing the recruitment of AHR to the FLG promoter region. In conclusion, pruritic HD patients had higher S. aureus colonization, with S. aureus‐secreted α‐toxin suppressing FLG expression through the AHR‐FLG axis.